ANALYSIS OF HALAL TOURISM DEVELOPMENT IN PAMEKASAN: ANALYTICAL NETWORK PROCESS APPROACH - R. Wahyu Agung Utama; Imron Mawardi (Universitas Airlangga, 2023)
This research aims to analyze problems, solutions, and strategic policies to support the development of halal tourism in Pamekasan by employing the Analytic Network Process (ANP) method. Data were obtained from nine experts consisting of representatives of academics, practitioners, associations, and regulators. Findings show that the most dominant issue is the aspect of human resources, followed by infrastructure, regulation, management, and marketing issues. Several strategic policies can be implemented to strengthen the development of halal tourism in Pamekasan, including (1) forming a team of mediators and regional tourism councils; (2) establishing halal tourism as a regional priority program; (3) increasing the capacity of Human Resources that involved in Halal tourism; (4) revitalizing tourism infrastructure and support its development; (5) increasing the diversification of halal tourism products; and (6) encouraging and facilitating halal certification. This research is expected to serve as a policy reference for decision-making, particularly in the development of Halal tourism. Further research could be conducted to investigate the implementation of halal tourism in Pamekasan; following the adoption of the RIPPDA Regional Regulation.